Developing 3D Animated Videos Using The Plotagon Story Application to Improve Arabic Listening Skills - Rokhani; Achmad Zuhriddin; M. Adib Zakariya; Sofy Ichsanudin Fachri; Muchammad Abdul Aziz; Nasih Burhani (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2024)
This research aimed to develop 3D animated videos using the Plotagon story application as a learning media for Arabic listening skills, test the effectiveness of the 3D animated videos developed to increase students’ interest and improve their Arabic listening skills. This research used Hannafin and Peck’s research and development model modified based on research needs. Research instruments included interviews, questionnaires, and tests. Data analysis techniques used were quantitative descriptive, one-sample t-test, and independent-sample t-test. The research results explained that the quality of the material and media of the 3D animated video developed using the Plotagon story application was very good. The video is effective in increasing students' interest in learning Arabic listening skills. Additionally, it helps them improve their Arabic listening abilities. It is possible to conclude that the production of multimodal input-based learning media using the Plotagon Story application can help students gain Arabic listening skills.